STUDY ON THE IMPACT OF MORAL DISENGAGEMENT ON EXAM MALPRACTICE AMONG STUDENTS IN THE EDO STATE (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Exam malpractice is a critical issue affecting educational institutions globally. Understanding the factors contributing to such unethical behavior is essential for effective prevention and intervention. One such factor is moral disengagement, which allows individuals to act unethically without feeling distress. This study investigates the impact of moral disengagement on exam malpractice among students in Edo State, Nigeria. A survey was conducted among 123 undergraduates from three public tertiary institutions in Edo State. The study utilized both descriptive and inferential statistics to analyze the data. The findings revealed that moral disengagement significantly influences students’ engagement in exam malpractice. The finding revealed a statistically significant, moderate positive correlation between disengagement dis and cheating behavior, r (121) = .44, p < .001. Importantly, moral disengagement explained 12.6% of the variation in cheating behavior. The finding has implications for educational and institutional development